NOTE ON THE DISTRIBUTION OF BIVALVE SPATS IN VELLAR ESTUARY - Jayabal, R; Kalyani, M (Indian Journal of Fisheries, 2011)
Survey was carried out over a stretch of 9 km of the estuarine shore forknowing the seed resources of bivalves in Vellar estuary and their seasonal distributions.Sediment samples, each from a 25 cm^ area at half-metre depth, werecollected at random between two consecutive stations. These samples were seivedusing a sieve of 0.5 mm mesh. Samples were then analysed in the laboratoryand the bivalve spats were quantitatively estimated and identified up to specieslevel. The spats at 3-5 nun size have the morphological characters of the adults.During the surveys salinity, dissolved-oxygen content and temperature werealso estimated at each sampling station